(Dis)connected Empires - Biedermann, Zoltán.
1 online resource (272 pages)
Keywords: (Dis)connected Empires offers a new contribution to the current debate on the role of global history in a world of resurgent nationalisms. Biedermann explores the world of early diplomatic connections between Europe and Asia in the Renaissance, focusing on the rarely told story of Portuguese encounters with the Buddhist kingdoms of Sri Lanka.